Clinical Characteristics and Side Effects of Multidrug Resistant Tuberculosis Therapy at Top Referral Hospital West Java Indonesia - Rahmawati, Rika Nurlaily; Pranggono, Emmy Hermiyanti; Ruslami, Rovina (Althea Medical Journal, 2016)
Background: The efficacy of multidrug resistant tuberculosis (MDR TB) therapy is still being questioned. It has lesser quality, longer duration therapy and high toxicity level. This study was conducted to identify clinical characteristics and side effect of MDR TB therapy at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia as the top referral hospital in West Java. Methods: A retrospective descriptive study was performed to 142 medical records of MDR TB inpatient and outpatient at Dr. Hasan Sadikin General Hospital from January 2012âJuly 2013. Data was collected on OctoberâNovember 2013. Data about clinical characteristics and side effects of MDR TB therapy were collected and was analyzed in the form of percentage.Results: From 142 patients, 96% had history of tuberculosis therapy. Eighty (56%) of them had positive acid fast bacilli (AFB) sputum that still remained after 5th month or more with category 2. Seventy (49%) patients used combination of pyrazinamide, capreomycin, levofloxacin, ethionamide and cycloserine (Pz-Cm-Lfx-Eto-Cs). All patients experienced side effects during therapy and the majority of them (91%) had gastroenteropathy and rheumatism. Tentamen suicide was detected in one patient. Conclusions: The MDR TB patients had history of tuberculosis therapy. The majority of patients used combination of Pz-Cm-Lfx-Eto-Cs. All patients experienced side effects during MDR TB therapy. [AMJ.2016;3(4):526â32]